Deciphering the microbial and genetic responses of anammox biogranules to the single and joint stress of zinc and tetracycline. (November 2019) - Fan, Nian-Si; Zhu, Xiao-Ling; Wu, Jing; Tian, Zhe; Bai, Yu-Hui; Huang, Bao-Cheng; Jin, Ren-Cun
Abstract: The feasibility of using anaerobic ammonium oxidation (anammox) process to treat wastewaters containing antibiotics and heavy metals was evaluated in this study. The nitrogen removal performance and characteristic parameters were monitored during the whole experimental period of 258 d. The single and joint effects of zinc and tetracycline on the microbial community were studied in upflow anaerobic sludge blanket (UASB) reactors. The anammox performance remained at levels comparable with the initial state at the lower inhibitor concentrations (zinc, 0–2.26 mg L − 1 ; tetracycline, 0–0.5 mg L − 1 ). When the concentrations of zinc and tetracycline increased to 3.39 mg L − 1 in R1 and 1.0 mg L − 1 in R2, an obvious deterioration in performance was observed. Dual inhibitors with a total concentration of ≥3 mg L − 1 caused dramatic decreases in the nitrogen removal efficiency of R3 . The quantification results showed that the abundances of eight antibiotic resistance genes (ARGs), czc A and int I1 in the experimental reactors generally increased under stress from metals or/and antibiotics, with final values higher than in the control, while the functional gene abundances were lower. Moreover, most genes exhibited significant correlations. Microbial community analysis indicated that Planctomycetes (represented by Candidatus Kuenenia) was inhibited by both zinc and tetracycline, but still held the dominant position. Furthermore, Caldilinea (belonging to Chloroflexi) maintained a higher abundance during the inhibitory period, implying its potential resistance to both inhibitors. These findings suggested that anammox could be inhibited by metals and antibiotics, but it has the potential to remove nitrogen from wastewaters containing both of them within the concentration threshold. Highlights: The inhibition thresholds of zinc and tetracycline on anammox were 3.39 and 1 mg L − 1, respectively. The joint inhibition of zinc and tetracycline on anammox was stronger than the single inhibition. Caldilinea was the potential resistance bacteria. Anammox has the potential to treat wastewaters containing small amounts of metals and antibiotics.